Improving Monitoring and Evaluation in the Civic Tech Ecosystem - Merlin Chatwin; John Mayne (JeDEM - eJournal of eDemocracy & Open Government, 2020)
For nearly a decade, civic tech stakeholders have been creating technology-supported solutions to civic challenges. Globally, the civic tech movement is rapidly professionalizing but has a limited history of documenting evidence of successes and challenges. Robust monitoring and evaluation in the civic tech ecosystem are necessary to create a foundation of knowledge for future initiatives. Monitoring plays a key role in improving services, pivoting approaches and guiding more efficient resource allocation. Evaluation highlights what is working, what is not working, and critically, why? In a sector that merges data, design and technology with user-centred principles, monitoring and evaluation in the civic tech ecosystem have several inherent challenges. This paper suggests that a theory-based evaluation approach called Contribution Analysis has the necessary sophistication and agility to support comprehensive monitoring and evaluation to support the growth and sustainability of the movement. This paper applies the early steps of contribution analysis to two Canadian civic tech projects to demonstrate its feasibility for civic tech.